2015
DOI: 10.1111/srt.12227
|View full text |Cite
|
Sign up to set email alerts
|

Tactile friction of topical formulations

Abstract: The present investigation shows that tactile friction measurements have potential as an alternative or complement in the evaluation of perception of topical formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…This friction hysteresis has not previously been observed on any of the other materials studied using our apparatus, which include paper [12], artificial skin [14], tissue and polymer. It was observed that on average the applied load in the backward stroke (all measurements) was 1.0 N while for the forward stroke this value was significantly larger at 1.5 N. When the finger encountered higher friction, a lower load was applied so that the finger could slide on the surface, most probably an unconscious action which has been addressed previously [12,15] and results from the fact that the tendency is to probe with a constant friction force, rather than constant load.…”
Section: Physical Characterisationsupporting
confidence: 48%
“…This friction hysteresis has not previously been observed on any of the other materials studied using our apparatus, which include paper [12], artificial skin [14], tissue and polymer. It was observed that on average the applied load in the backward stroke (all measurements) was 1.0 N while for the forward stroke this value was significantly larger at 1.5 N. When the finger encountered higher friction, a lower load was applied so that the finger could slide on the surface, most probably an unconscious action which has been addressed previously [12,15] and results from the fact that the tendency is to probe with a constant friction force, rather than constant load.…”
Section: Physical Characterisationsupporting
confidence: 48%
“…A physical characterization of the rheological, mechanical, and tribological properties of preparations is therefore necessary to understand their behavior under different stresses (ease of removal of product from the container, good spreadability on skin, acceptable viscosity …) and optimize their design. Such tools are complementary to sensory analysis and made possible to deeply characterize the textural properties of formulations and predict their performances during the use for topical application …”
Section: Introductionmentioning
confidence: 99%
“…Such tools are complementary to sensory analysis and made possible to deeply characterize the textural properties of formulations and predict their performances during the use for topical application. [14][15][16] The present work focused on a range of commercial topical products, selected with various compositions and galenic forms either gel or emulsion. They were analyzed using sensory analysis, rheology, texture analysis, and a frictiometer in order to develop a non-subjective characterization of the tactile properties of topical products.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the behaviour of finger tactile friction in different environments will deepen our understanding of the mechanisms involved in tactile perception and, therefore, be helpful for optimizing hand-operated activities under liquid and moist conditions [13], as well as for the design and operation of intelligent robots in a liquid environment. Also, it would be beneficial for research and development of cosmetic products, such as moisturizers and lotions [14][15][16][17]. Finally, finger-based tactile testing is used as a nonoral based method to characterize oral perception because of the similar sensory assessment of tactility and food texture [11,18].…”
Section: Introductionmentioning
confidence: 99%